On the use of entropic regularization for identification of cohesive crack parameters. - Que, Norbert S. (Philippine engineering journal.)
The fracture parameters governing the cohesive crack model is obtained through the use of entropic regularization. Specifically, it is employed as a smoothing technique that lends to the solution of a difficult identification problem cast as a mathematical program with equilibrium constraints (MPEC). Results suggest that reformulation of MPEC as a nonlinear programming problem using entropic regularization show promise in the solution of the parameter identification problems considered in this paper.